Linear body measurements as a management tool for Tunisian local goat population raised in arid conditions - Ahlem A.; Laroussi A.; Abdennebi M.; Ben Salem F (Pastoralism and sustainable development: proceedings, 2021)
The study aims to describe the linear body measurements and their factors of variation, and to establish their possible relationship. The morphostructural parameters for 92 local kids,including the body length, the wither height, the paunch girth, the heart girth and the rump length,were collected from birth to 150 days of age. The mean body length of male was 39.80cm, while that of the female was 38.27cm. Similarly, the heart girth as well as the wither height was also higher (p<0.05) in male than those in female. This trend confirms sexual dimorphism in local kids. The type of birth has non-significant effect on paunch girth. A high correlation (r=0.90) was recorded between the paunch girth and the heart girth.This is the same for the correlation between the height at the withers and the body length. Both, the body length (r=0.97) and the wither height (r=0.95) presented the highest correlations with live body weight. It could be concluded that the weight of local kids can be predicted with accuracy from some body measurements such as the heart girth which can be exploited by goat producers for management, selection and genetic improvement programs in local goat population.
International e-Workshop organized in the framework of PACTORES project, 2021/07/14-15, Valenzano, Bari, (Italy)